Written production in learner French - Lindqvist, Christina (University of Gothenburg, 2025)
This corpus contains student texts. Swedish lower secondary school students aged 11-15 (years 6, 7, 8 and 9) were invited to retell a short story ("The Dog Story") in writing. The data were collected during an ordinary French lesson. The students had 20 minutes to write the text. They were encouraged to write as much as they could and to focus on communicating the content.
The texts were originally written by hand and transferred manually to Word-documents. The documents were later converted to plain text using LibreOffice 7.4 (command: 'soffice --headless --convert-to txt:Text YOUR-DOCUMENT-HERE.DOC').
For access to the corpus, contact Christina Lindqvist (christina.lindqvist@sprak.gu.se).

Denna korpus innehåller elevtexter. Svenska högstadieelever i åldrarna 11-15 (år 6, 7, 8 och 9) fick i uppgift att återberätta en bildserie ("The Dog Story") skriftligt. Datan samlades in under en vanlig lektion i franska. Eleverna hade 20 minuter på sig att skriva texten. De uppmuntrades att skriva så mycket de kunde och att fokusera på att kommunicera innehållet.
Texterna skrevs ursprungligen för hand och överfördes sedan manuellt till Word-dokument. Dokumenten konverterades därefter till ren text med hjälp av LibreOffice 7.4 (kommando: 'soffice --headless --convert-to txt:Text YOUR-DOCUMENT-HERE.DOC').
Kontakta Christina Lindqvist (christina.lindqvist@sprak.gu.se) för att få tillgång till korpusen.
Skriftlig produktion i inlärarfranska
Keywords: Language Technology (Computational Linguistics); French; L2; foreign language; written production; corpus; Natural Language Processing; Språkbehandling och datorlingvistik